ADDICTION TO TOBACCO, WINE, DRUGS BY THE ADOLESCENT OF WEST BENGAL - Ka, Saikat Kumar; Bose, Dibakar; Bose, Dibakar; Kumar, Chandan; Banerjee, Kaushik Banerjee; Banerjee, Kaushik (International Journal of Psychosocial Rehabilitation, 2020)
Addiction is the biggest problem of the nation in 21st century .Recent clock time we observe the addiction to tobacco , wine, gutkha are increasing among the understudy are maturation Clarence Day by day. So we conducted this survey at siliguri to find out the dependence problem in local sphere among the understudies. As our survey revealed that maximum number of understudies are having this type of habit & also shocking that both the gender have this problem. Result of the survey are based on 926 responder of understudies of boys and girls. Observation also revealed that their family, even teachers and friend are mostly responsible for this. Fixture counseling time of year both on primary winding and higher education institute are required to solve this problem of the siliguri, not only the understudies their family phallus participance in those session is also required. Giving caliber education should not be the only parametric quantity In schools & colleges rather than their nidus should be make every student a good man being as well as springiness quality education and more importantly make siliguri a addiction of bad habits free education hub.